Evaluation of the effectiveness and usability of an educational portion size tool, ServARpreg, for pregnant women. Issue 6 (24th April 2019) - Brown, H. M.; Collins, C. E.; Bucher, T.; Rollo, M. E.
Abstract: Background: Elevated blood glucose levels in pregnancy increases the risk of adverse pregnancy outcomes. Modifying consumption of carbohydrate‐rich foods is important for blood glucose regulation; however, the tools commonly used to assist in guiding portion control are impractical. The present study aimed to evaluate usability of ServARpreg, a mobile phone‐based nutrition tool, and its effectiveness with respect to improving carbohydrate and standard serve size knowledge in pregnant women. Methods: A baseline survey assessed knowledge of carbohydrates and standard serve sizes of pregnant women. A subset of women living in Newcastle were invited to use ServARpreg, containing pregnancy nutrition information and augmented reality guidance on portion control. A follow‐up survey was sent to all women 4 weeks after baseline and women who received ServARpreg also received a process evaluation survey after 10 weeks. Results: Responses were received from 186 pregnant women for the baseline survey, with 97 completing the follow‐up (52.2%). Of the 56 women eligible to receive ServARpreg in the sub‐study, 47 accepted (83.9%) and, of these, 40 completed the process evaluation survey (85.1%). At follow‐up, there was a significant group × time interaction in favour of the ServARpreg group for carbohydrate quantification knowledge ( F 1, 279 = 9.705, P = 0.002). Standard serve size knowledge did not change between groups. In the process evaluation survey, 80% strongly agreed/agreed that ServARpreg made them more aware of how much they ate and 72.5% found ServARpreg easy to use. Conclusions: ServARpreg has shown potential to educate pregnant women about carbohydrate quantification and increase portion size awareness. Further refinement of the tool and evaluation is needed to improve standard serve size knowledge.